Involvement of proinflammatory S100A9/A8 in the atherocalcinosis of aortic valves - R. А. Moskalenko; А. M. Romaniuk; I. O. Iashchishyn; I.-M. S. Zakorko; А. M. Piddubnyi; Ye. O. Chernov; L. O. Morozova-Roche (Patologìâ)
Abstract